A note on finite time blowup for dissipative Klein–Gordon equation. (June 2020) - Pang, Yue; Yang, Yanbing
Abstract: This is a continuation of the study on an arbitrarily positive initial energy finite time blowup result of the solution to the initial value problem of strongly damped Klein-Gordon equation. Based on an adapted concavity method, both the conclusions and arguments of the present paper are not bounded by the coefficients of dissipative damping terms.